Predictors of malnutrition among under-five children in internally-displaced person camps of Adamawa and Yobe states, Nigeria - Mela, Fatima Dahiru (2020)
Introduction: Malnutrition was described as imbalances, excesses, or deficiencies in the intake of nutrients by an individual. Globally, malnutrition is the key factor of disease burden among under-five children. In Africa, malnutrition in under-five children showed 59 million as stunted 14 million as wasted, and 10 million were overweight. Nigeria is among the six countries of the world where half of all the death among under-five children was due to malnutrition. In addition, the failure to have adequate dietary intake was borne out of demolition of farming activities, as well as inability to reach good health care services, water supply. It is against this background that lead to rise in the rate of malnutrition among children in the IDP camps. Based on literature searched, there was no study conducted on predictors of malnutrition among under five children in the IDP camps of Adamawa and Yobe States, Nigeria hence the need to conduct the research. Objective: To determine the predictors of malnutrition (stunting, wasting and underweight) among under-five children in IDP camps of Adamawa and Yobe states, Nigeria. Methods: An analytical cross-sectional study was conducted among 807 children aged 6 to 59 months from the three IDP camps from September 2018 to January 2019. A probability proportionate to size was used to select the sample size from each IDP camp, after which a single random table number was used to select the participants from the list of under-five children. A self-guided structured questionnaire was administered to collect information on sociodemographic characteristics, parental factors, child information, food consumption, environmental factors as well as the anthropometric measurement of both the children and caregivers. Descriptive analysis, chi-square test statistics, simple and binary logistic regression analyses were used, and the level of significance was set at p< 0.05. Result: The overall prevalence of stunting, wasting, and underweight were 17.1%, 40.9%, and 29.7% respectively. The predictors of stunting were age of the child (AOR=3.275; 95% CI=1.954-5.489, p=<0.001) and symptoms of watery stool in the last 2 weeks (AOR=0.648; 95% CI=0.429-0.979, p=0.039). For wasting the predictors are mother’s occupation (AOR=1.494; 95%CI=1.101-2.026, p=0.010), age of the child (AOR=2.359; 95% CI=1.699-3.275; p<0.001), gender of the child (AOR=0.667; 95% CI=0.491-0.905; p=0.009), symptoms of watery stool in the last 2 weeks (AOR=0.467; 95% CI=0.283-0.773; p=0.003). Whereas the predictors of underweight were mother’s occupation planning (AOR=0.708; 95% CI=0.511-0.983; p=0.039), age of the child (AOR=1.458; 95% CI=1.008-2.108; p=0.045), gender of the child (AOR=1.983; 95% CI=1.430-2.748; p<0.001), symptoms of watery stool in the last 2 weeks (AOR=1811; 95% CI=1.271- 2.582; p =0.001), weight of the mother (AOR=0.714; 95% CI=0.515-0.990, p=0.043), household income (AOR=0.712; 95% CI=0.510-0.994; p=0.046), birth weight of the child (AOR=1.685; 95% CI=1.031-2.755; p=0.038). Conclusion: The study found that socio-demographic characteristics of the caregivers, parental factors, child information, and environmental factors were significantly associated with stunting, wasting, and underweight among under-five children in the IDP camps. It, therefore, needs a multisectoral collaboration such as ministry of agriculture, health, education, and finance to address the malnutrition in the IDP camps of Nigeria, and the identified predictors of malnutrition among the under-five children should be included in the future programs that would address all the three indices of malnutrition.